Implementasi Pendekatan Pembelajaran Kontekstual dalam Peningkatan Kemandirian Belajar Siswa (Studi Literatur) - Servista Bukit (Jurnal Multidisiplin Madani, 2022)
This study aims to determine the application of Contextual Teaching Learning (CTL) in the learning process. This research is a literature study, which aims to determine the application of contextual learning approaches in learning in fostering student learning independence. In this study, the researcher first formulates the problem, then proceeds to explore existing and relevant research for analysis. Data collection techniques by browsing electronic journals, theses, and under theses through Google Schoolar. From the research results of 20 relevant articles, it shows that the CTL approach is very effective in increasing students' learning independence. This is because the CTL approach encourages students to construct their knowledge by applying it in everyday life as members of the family and community.